AN ANALYSIS OF WORD FORMATION IN JARGONS USED BY MIDWIFE IN RANDUAGUNG MATERNITY CENTER - BUDIHARJO, NICO EKA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Sociolinguistics is the study about language used in society. It deals withvarieties of language in society such as jargon. Jargon is specialized vocabulary or terms in spoken or written text used by certain profession or other group. The objectives of the study are to identify or to describe the jargon and their word formation processes used by midwife in Randuagung maternity center.This research applied qualitative approach because the analysis was in the formof description rather than number. By analyzing data qualitatively, the writer described jargons about midwifery obtained from the midwife in Maternity Center Randuagung. Furthermore, in analyzing the data, the writer used two steps of analysis process which were organizing and interpreting.There were some word formation processes found in this study. The processeswere acronym, derivation, borrowing, clipping and compounding. The results of this study showed that total of the jargons found were 53 jargons used by midwife in Randuagung maternity center. They were 5 jargons of acronym, 3 of derivation, 22 of borrowing (17 jargons were direct borrowing and 5 jargons were indirect borrowing), 2 of clipping and the last 21 jargons of compounding. English and Latin are dominant languages in constructing the jargon of medical in this case in midwifery, so that the jargons of midwifery often use both of languages. It showes that communication codes in midwifery jargon are supposed to be more simple and acceptable. In addition, the jargons must be translated into Indonesia language to understand the meaning.The writer suggests future researchers to do more studies in the field of jargonsand word formation processes from different sources and data. Keywords: Sociolinguistics, Jargons, Word formation, Midwife in Maternity CenterRanduagung.